Age related studies on the dehydrogenases of the testis in Assam goat - SARMA, KAMAL; KALITA, S N; SARMA, M; DEVI, J (The Indian Journal of Animal Sciences, 2012)
Male Assam goats (18) varying in age from 0-day to 10 months were used in the present study. The animals were divided into groups, viz. group 1 (0-day), 2 (2 months), 3 (4 months), 4 (6 months), 5 (8 months) and 6 (10 months) consisting of 3 animals in each group. The cryostat sections were incubated for the histoenzymic demonstration of various enzymes viz. glucose-6-phosphate dehydrogenase (G-6-PDH), lactate dehydrogenase (LDH), malate dehydrogenase (MDH), Δ5-3 ß-hydroxysteroid dehydrogenase (Δ5-3 ß-HSD) and 17-ß-hydroxysteroid dehydrogenase (17-ß-HSD). The seminiferous tubular epithelium of the testis in day-old (group 1) and 2-month old (group 2) kids showed mild activity of LDH enzyme which increased to moderate at 4 months of age (group 3) and moderate to strong in 6- and 8-month old goats (groups 4, 5). The activity of MDH remained weak in the seminiferous epithelium up to 4 months of age (group-3), increased to moderate in 6- month-old bucks (group 4) and strong in older goats. The activity of G-6-PDH was weak in the seminiferous epithelium at all the ages except at 8 and 10 months of age (groups-5, 6), in which a moderate activity of this enzyme was seen. The activities of 17-ß-HSD and Δ5-3ß-HSD were absent in the seminiferous epithelium in all the animals. These enzymes showed moderate to intense activities in the leydig cells from 6–10 months of age (groups 4 to 6). Similarly, LDH, MDH and G-6-PDH exhibited moderate activity in the Leydig cells of male kids at 4 month of age and the activity increased with advancing age of the male goats.